2020
DOI: 10.3390/ijms21218276
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in Water Soluble Carbohydrate Components in Leaves and Sucrose Associated TaSUT1 Gene Expression during Grain Development in Wheat

Abstract: In plant tissues, sugar levels are determined by the balance between sugar import, export, and sugar synthesis. So far, water soluble carbohydrate (WSC) dynamics have not been investigated in a diurnal context in wheat stems as compared to the dynamics in flag leaves during the terminal phases of grain filling. Here, we filled this research gap and tested the hypothesis that WSC dynamics interlink with gene expression of TaSUT1. The main stems and flag leaves of two genotypes, Westonia and Kauz, were sampled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The accumulation, metabolism, and transport of sugars, and especially those of sucrose, are strongly dependent on both environmental and physical parameters such as temperature, CO 2 , photoperiod, and the circadian rhythm as well as interactions with plant hormones. Four articles discussed the implication of cold, photoperiod, and hormonal control in soluble sugar and sucrose contents in relation to plant development phases [26][27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation, metabolism, and transport of sugars, and especially those of sucrose, are strongly dependent on both environmental and physical parameters such as temperature, CO 2 , photoperiod, and the circadian rhythm as well as interactions with plant hormones. Four articles discussed the implication of cold, photoperiod, and hormonal control in soluble sugar and sucrose contents in relation to plant development phases [26][27][28][29].…”
mentioning
confidence: 99%
“…Thus, addressing the diurnal patterns of sugar transport in wheat during the period of grain filling is of major concern. Al-Sheikh Ahmed et al [29] investigated the possible diurnal changes in water-soluble carbohydrates that occur in correlation with different expression levels of the sucrose transporter TaSUT1 gene in two different wheat varieties, Kauz and Westonia. It was suggested that a higher expression of TaSUT1 in leaves that correlates well with the high sucrose levels observed in the variety Kauz can contribute to a grain weight increase in this variety.…”
mentioning
confidence: 99%
“…Additionally, the migration of the active component to the food simulant is affected by the polarity of the migrant and simulating media. Also, the sum of glucose, fructose, sucrose, and fructans is termed “water soluble carbohydrate” (Al-Sheikh Ahmed et al 2020 ). Phillips et al ( 2009 ) confirmed this result by comparing the antioxidant activity content among natural sweeteners (fruit sugars, e.g., date sugar) versus refined sugar and found that date sugar has the highest antioxidant activity of the natural sweeteners studied.…”
Section: Resultsmentioning
confidence: 99%